Experimental Study of Effects of Variation Use Fuel type On Exhaust Emissions With Loads 500,1050,2000 watt generator - Reynaldy Reynaldy (Bandar Lampung University (UBL), 2017)
Electricity is the energy needed by the human subject. Planning Director of PT PLN (Persero) Nicke Widyawati say, until 2017 thiscapacity electricinstalled new nationally has 53 585 MW of electrical capacity. Our electrification ratio remained at 81.5%, or about 40 million people untapped power facilities. Research titled